2006
DOI: 10.1002/star.200600498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Radiation on the Physicochemical Properties of Normal Maize, Waxy Maize and Amylomaize V Starches

Abstract: Normal maize, waxy maize and amylomaize V starches were treated at a moisture content of 30% by microwave radiation. The results showed that the surface was porous and a cavity could be clearly observed at the center of the three starches. Microwave treatment increased the X‐ray intensities of the major d‐spacings of all starches and changed the X‐ray pattern of amylomaize V from B to A+B. The swelling power (amylomaize V < normal maize < waxy maize) and solubility (amylomaize V < normal maize < waxy maize), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 11 publications
7
89
0
Order By: Relevance
“…Microwave treatment on starch were carried out especially on samples with high water content, over 20%, and less on samples with low (1 -5%) or limited (7 -15%) moisture content. The results showed that microwaves may determine the rearrangement of intermolecular structure indicating that the starch granule structure is disintegrated and, consequently, they lead to slight reduction of the water absorption ability, of solubility and swelling power as well as changes of the gelatinization temperature, syneresis or paste viscosity (Lewandowicz et al, 1997;Lewandowicz et al, 2000;Gonzalez & Perez, 2002;Gonzalez Parada & Perez Sira, 2003;Szepes et al, 2005;Luo et al, 2006;Lares & Perez, 2006) strongly correlated with experimental treatment parameters. Starch exposed to electrical discharges (plasma) may suffer either crosslinking phenomenon (Zou et al, 2004 or depolymerization to dextrins with different molecular weights (Lii et al, 2002a;Lii et al, 2002b) …”
Section: Introductionmentioning
confidence: 86%
“…Microwave treatment on starch were carried out especially on samples with high water content, over 20%, and less on samples with low (1 -5%) or limited (7 -15%) moisture content. The results showed that microwaves may determine the rearrangement of intermolecular structure indicating that the starch granule structure is disintegrated and, consequently, they lead to slight reduction of the water absorption ability, of solubility and swelling power as well as changes of the gelatinization temperature, syneresis or paste viscosity (Lewandowicz et al, 1997;Lewandowicz et al, 2000;Gonzalez & Perez, 2002;Gonzalez Parada & Perez Sira, 2003;Szepes et al, 2005;Luo et al, 2006;Lares & Perez, 2006) strongly correlated with experimental treatment parameters. Starch exposed to electrical discharges (plasma) may suffer either crosslinking phenomenon (Zou et al, 2004 or depolymerization to dextrins with different molecular weights (Lii et al, 2002a;Lii et al, 2002b) …”
Section: Introductionmentioning
confidence: 86%
“…A total weight of 3.0 mg of starch samples (db) and distilled water (1 : 2, w/w) added with a microsyringe to corn starch in pre-weighed aluminium sample pans. The pan was hermetically sealed and allowed to equilibrate for 12 h before analysis (Luo et al 2006;Klein et al 2013). The time was enough for the hydration of corn starch examples.…”
Section: Methodsmentioning
confidence: 99%
“…Extrusion weakened the crystalline structure within starch particles and the double helix unwinding after extrusion processing . Emulsifier combined the unwinding of the double helix formed a different type of amylose emulsifier complexes and then reaggregation occurred, which caused a different rise in gelatinisation temperature (Bhatnagar & Hanna 1994;Luo et al 2006;. The increased gelatinisation temperature was attributed to structural changes within the starch particles, which involved amylose-amylose and amylase-lipid interactions (Da Rosa Zavareze & Dias 2011).…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…This can be observed in the loss of birefringent properties and in the swelling of the starch granules. Luo et al (2006) conducted a study to investigate changes in crystallinity, swelling power and solubility, gelatinization parameters, retrogradation characteristics, and pasting properties of corn starches at 30% moisture after being subjected to microwave heating at 1 W/g microwave energy for 20 min. Microwave heating could convert starch directly to glucose in a relatively short time.…”
Section: Effect Of Microwave-assisted Hydrolysis In Dilute Acidmentioning
confidence: 99%